The Relationship between Exercise Behavioral Skills and the Stages of Change for Exercise Behavior among Japanese Adults - NAKAMURA, Yoshio; SAKAI, Kensuke; TAKEDA, Noriko; OKA, Koichiro (Japanese Journal of Behavioral Medicine, 2009)
The present study was intended to develop the Exercise Behavioral Skills (EBS) questionnaire and to determine the relationship between exercise behavioral skills and the stages of change for exercise behavior. An initial pool of items was generated based on the behavioral processes of change and several behavioral techniques for exercise behavior change. In all, 647 community residents of 20-years-old or older answered a questionnaire. Explanatory factor analysis results yielded a questionnaire comprising one factor with five items. Psychometric analyses showed that the questionnaire has high consistency and validity. The relationship between the EBS score and the stages of change for exercise behavior was also investigated. Analysis of variance showed that the score was significantly associated with the stages of change. Especially, scores were lower for subjects in precontemplation compared to other stages and were higher for subjects in action and maintenance compared to those of subjects in contemplation and preparation. Results indicate that the use of the behavioral skills depends on an individual's stage of change for exercise behavior. Exercise behavioral skills are available as information for enhancing exercise adoption and maintenance.